2018
DOI: 10.2147/copd.s153200
|View full text |Cite
|
Sign up to set email alerts
|

Clinical impact of episodic nocturnal hypercapnia and its treatment with noninvasive positive pressure ventilation in patients with stable advanced COPD

Abstract: PurposeEpisodic nocturnal hypercapnia (eNH) caused by rapid eye movement (REM) sleep-related hypoventilation is often noted in patients with advanced COPD. The purpose of this study was to clarify the clinical significance of eNH and the effectiveness of eNH-targeted noninvasive positive pressure ventilation (NPPV).Patients and methodsWe enrolled patients with stable, severe, or very severe COPD with daytime arterial partial oxygen pressure PaO2 ≥55 mmHg and daytime arterial partial carbon dioxide pressure PaC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 34 publications
(45 reference statements)
0
19
0
Order By: Relevance
“…In the recent HOT-HMV trial, there was a statistically significant reduction in nocturnal P tcCO 2 levels on the night after initiation of NIV, which reportedly persisted to 12 months [62]. Finally, uncontrolled nocturnal hypoventilation seems to be related to increased risk of exacerbations and pulmonary hypertension [121]. End tidal carbon dioxide monitoring should never be used to approximate P aCO 2 in patients with COPD during spontaneous breathing or NIV, and is even less reliable in patients with invasive ventilation [122,123] In recent years, improvements introduced by manufacturers in their models have led these devices to act both as ventilators and monitors.…”
Section: Narrative Question 2: How Can Clinicians Monitor and Follow-mentioning
confidence: 95%
“…In the recent HOT-HMV trial, there was a statistically significant reduction in nocturnal P tcCO 2 levels on the night after initiation of NIV, which reportedly persisted to 12 months [62]. Finally, uncontrolled nocturnal hypoventilation seems to be related to increased risk of exacerbations and pulmonary hypertension [121]. End tidal carbon dioxide monitoring should never be used to approximate P aCO 2 in patients with COPD during spontaneous breathing or NIV, and is even less reliable in patients with invasive ventilation [122,123] In recent years, improvements introduced by manufacturers in their models have led these devices to act both as ventilators and monitors.…”
Section: Narrative Question 2: How Can Clinicians Monitor and Follow-mentioning
confidence: 95%
“…As mentioned above, during REM sleep, desaturation tends to be caused by enhanced alveolar hypoventilation (socalled REM sleep-related hypoventilation) and exhibits the characteristic SpO2 pattern (14)(15)(16)(17). We assume that the clinical condition of the periodic pattern reflects this REM sleep-related hypoventilation because it showed that the SpO2 dropped at a cycle of approximately 90-120 minutes, and the waveform was similar to that mentioned in previous reports (14)(15)(16). O'Donoghue et al (18) reported that REM sleep-related hypoventilation was associated with daytime PaCO2 and a high BMI, but our study did not support their findings.…”
Section: Discussionmentioning
confidence: 99%
“…In other words, it is possible that patients in this group might be exposed to severe hypoxemia regardless of the severity of COPD. Even in patients with COPD without daytime hypoxemia, it has been reported that desaturations can occur due to complications such as obstructive sleep apnoea (OSA) and rapid eye movement (REM) sleep-related hypoventilation [ 19 , 20 ]. It is suggested that there is a population exposed to severe hypoxemia due to overlap of pathophysiologies, such as apnoea and hypoventilation.…”
Section: Discussionmentioning
confidence: 99%